Sweet and sour : life-worlds of Taipei women entrepreneurs - Simon, Scott, 1965- (Asian voices (Rowman and Littlefield, Inc.), 2003)
Sweet and Sour is the first in-depth anthropological study of Taiwanese women entrepreneurs, their career ambitions, their family relations, and their projects of self-identity. Focusing on the voices and perspectives of the women themselves, Scott Simon draws from life-narratives of women from various ages, ethnic groups, social classes, and occupations to provide a diverse set of rarely heard native voices speaking out on gender and entrepreneurship in Taiwan. This rich collection of life histories provides a unique understanding of Taiwa.